Ceria Mentari: Cerita Rakyat Terpopuler (Most Popular Indonesian Folklore) Applications with Augmented Reality - Senny Luckyardi; Citra Nurimbono; Shafira Hardian Alkhoir; Putri Khairunnisa Salsabila (International Journal of Research and Applied Technology (INJURATECH), 2022)
This study aims to design educational and entertainment media for children and adolescents using Augmented Reality technology. The research method used in this study is a qualitative descriptive analysis. At the same time, in the process of application development, Ceria Mentari adopts the object-oriented method and Multimedia Development Life Cycle prototype (MDLC). The results showed that the design of the Ceria Mentari application could provide a new experience for children in reading folklore through digital devices. The central concept of this application is to make children feel closer to folklore characters through the medium of Augmented Reality (AR), which can provide a sense of interactive learning. In the end, this application emerged as an information medium in the form of dynamic visual media to adapt to the new habits of the world of education, especially in kindergartens and elementary schools.